Peraturan Tentang Mezbah didalam Keluaran 20: 22-26 - Riska Nadeak; Kusnanto Tri A Nainggolan; Widya Novita Hutabarat; Herdiana Boru Hombing (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2023)
Summary Worship in the Christian sense is God's commandment, which must be fulfilled by everyone who is redeemed and saved through the Lord Jesus Christ. The purpose of the study is to answer: What is meant by the worship of a believer? According to the Bible, what are the components of worship? How do you live worship in the church life? This study used a qualitative method with a library research approach. The results of this study are: (1) True worship is serving God by offering various acts and attitudes of respect and adoration, submission and obedience with gratitude to the whole body, soul and spirit. (2) The elements of worship are an expression of the human mind which acknowledges that God is sovereign, full of power, and full of goodness. With a series of personal and human sacrifices approaching the altar of God with sacrifices. (3) Worship is lived in the life of the church with Jesus as the object of worship through hymns of praise, prayer, confession of sins, forgiveness, thanksgiving. The church life consists in offering the best sacrifices to God, that is body, soul.